Deskripsi Potensi Sumber Daya Manusia dalam Upaya Meningkatkan Capaian Kontrasepsi Mantap di Kota Surabaya Tahun 2014–2016 - Ratih Nur Hayati; Nurul Fitriyah (Universitas Airlangga, 2017)
Population problems are characterized by an increasing rate of rapid population growth (BKKBN, 2012). Family planning program is the government’s spearhead to control population growth. Surabaya City which consist of five regions has diverse characteristics of population, ranging from different levels of Education 2015 (71.95%) and exceeding Surabaya’s achievement target by 70% (Dinkes Surabaya, 2015). However, increased achievements of MOW and MOP acceptors in the following year were not guaranteed. Based on those statements, the identification of resource potency to increase the achievement of permanent contraception method was performed. The resource data was the achievement data of Surabaya in 2014–2016. The objective of this study was to describe resource potency to increase MOP and MOW achievement in Surabaya based on achievement data in 2014–2016. The secondary data, namely permanent contraception data was obtained from KB Sector in Department of Population Control, Women Empowerment and Child Protection of Surabaya City and adjusted with the amounts of available midwives, KB staffs and health care facilities in each district. Based on the data analyzed, it was found that resource potency from available midwives, KB staffs and health care facilities had potential effect on permanent contraception achievement in 5 Surabaya’s regions. It was recommended to give IEC involving religion leader or public figure with high influence on public to perform persuasive effort to other acceptors.